Fine-scale vegetation use by white-tailed deer in a forested landscape during hunting season. Issue 6 (1st November 2020) - Henderson, Colby B.; Demarais, Stephen; Street, Garrett M.; Strickland, Bronson K.; McKinley, William T.
ABSTRACT: Some prey species use hiding tactics and thus select areas that provide greater visual obstruction for predator avoidance, and vegetative characteristics that provide greater obstruction should be selected. To investigate vegetative characteristics selected by adult male white-tailed deer ( Odocoileus virginianus), we compared vegetation between heavily used and unused areas within home ranges of 22 adult (2.5+ years old) males during 1 November 2017–30 January 2018, which coincides with the Mississippi modern-firearms hunting season and includes breeding season. Vegetation within heavily used cells was 20% taller and provided 56% greater Nudds screening cover and >120% greater coverage of thicket and herbaceous plants. Four of seven vegetation variables were influential towards selection in heavily used areas: canopy coverage of thicket-producing, herbaceous, live woody, and dead woody plants. Basal area, height of vegetation, and Nudds board values were not influential. Exclusion of Nudds values from the model suggests adult males selected vegetative characteristics that provided more than just physical obstruction. Forest managers can use these results in inform management actions to attract adult male deer.